2012
DOI: 10.2478/v10181-012-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose experimental zearalenone intoxication on the immunoexpression of estrogen receptors in the ovaries of pre-pubertal bitches

Abstract: Zearalenone is an estrogenic mycotoxin that often contaminates plant material used in the production of feeds for companion animals. Small daily doses of ingested zearalenone -a competitive substrate modulating the activity of enzymes participating in estrogen biosynthesis at the pre-receptor level -can induce subclinical symptoms of hyperestrogenism in bitches. The objective of this study was to determine the effects of low zearalenone doses on the presence of estrogen receptors in the ovaries of pre-pubertal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…In view of the characteristic properties of oestrogen, it could be inferred that the administration of ZEN induced the presence of large calcium deposits in the mitochondria, cellular debris, and residual oocytes in group EII. In another work (Gajęcka 2012) we have found the absence of a positive response to the presence of estrogen receptors ERα and results obtained in both experimental groups suggested that long-term exposure to low-dose ZEN intoxication decreased the positive response of ERβ receptors in the ovaries of experimental bitches, which initiated epigenetic modification mechanisms that inhibited (rather than regressed) the ovarian development.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the characteristic properties of oestrogen, it could be inferred that the administration of ZEN induced the presence of large calcium deposits in the mitochondria, cellular debris, and residual oocytes in group EII. In another work (Gajęcka 2012) we have found the absence of a positive response to the presence of estrogen receptors ERα and results obtained in both experimental groups suggested that long-term exposure to low-dose ZEN intoxication decreased the positive response of ERβ receptors in the ovaries of experimental bitches, which initiated epigenetic modification mechanisms that inhibited (rather than regressed) the ovarian development.…”
Section: Introductionmentioning
confidence: 99%
“…ZEN affinity for ERβ of varies concentrations and the phase of the estrous cycle (Hatoya et al 2009). Locations of ER subtypes in the ovaries of various animal species reported by Korach et al (2003) and in our previous study (Gajęcka 2012) indicate that the changes observed in ovarian tissues could be induced by ZEN and α-ZOL effects on ERβ in the ovaries. It should also be noted that an increase in ZEN concentrations in feed is accompanied by a decrease in ERβ in ovarian tissues (Gajęcka 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Locations of ER subtypes in the ovaries of various animal species reported by Korach et al (2003) and in our previous study (Gajęcka 2012) indicate that the changes observed in ovarian tissues could be induced by ZEN and α-ZOL effects on ERβ in the ovaries. It should also be noted that an increase in ZEN concentrations in feed is accompanied by a decrease in ERβ in ovarian tissues (Gajęcka 2012). The above could imply that congestion in the ovarian cortex is caused by non-genomic effects of estrogens (Bishop and Stormshak 2008).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations